Criticism on the Turkish Translation of the Dewey Decimal Classificiation's 20th Standart Edition - Erol Pakin (Türk Kütüphaneciliği)
Concerning the Turkish translation of the Dewey Decimal Classification's 20th edition, critical thoughts and some of the ascertained deficiencies about the terms used in general, the methods used in the field of language and literature and the subjects scheme of Islamic Religion are pointed out and explained.